2009
DOI: 10.1073/pnas.0906649107
|View full text |Cite
|
Sign up to set email alerts
|

Gene amplification confers glyphosate resistance in Amaranthus palmeri

Abstract: The herbicide glyphosate became widely used in the United States and other parts of the world after the commercialization of glyphosate-resistant crops. These crops have constitutive overexpression of a glyphosate-insensitive form of the herbicide target site gene, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS). Increased use of glyphosate over multiple years imposes selective genetic pressure on weed populations. We investigated recently discovered glyphosate-resistant Amaranthus palmeri populations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
868
5
18

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(956 citation statements)
references
References 39 publications
35
868
5
18
Order By: Relevance
“…From another standpoint, Gaines et al (2010) Collectively, the data presented herein leads to the conclusion that the Brazilian Detection of glyphosate-resistant palmer amaranth ...…”
Section: Results E Discussionmentioning
confidence: 99%
“…From another standpoint, Gaines et al (2010) Collectively, the data presented herein leads to the conclusion that the Brazilian Detection of glyphosate-resistant palmer amaranth ...…”
Section: Results E Discussionmentioning
confidence: 99%
“…Analysis of fluorescence in situ hybridization has shown that EPSPs gene copies were present on almost all chromosomes of the genome of A. palmeri and appeared to be distributed randomly (Gaines et al, 2010). The high number of copies and their location on the genome suggests the action of transposon-like proteins or RNAmediated mechanisms.…”
Section: Gene Amplificationmentioning
confidence: 99%
“…Another mechanism for glyphosate resistance was identified recently in biotypes of Amaranthus palmeri from Georgia, USA (Gaines et al, 2010). The number of EPSPs gene copies in susceptible population ranged Table 2 -Glyphosate resistance mechanisms identified in 11 weed species from 1 to 1.3, whereas in resistant biotype this number ranged from 5 to more than 160 copies of the gene.…”
Section: Gene Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyphosate resistance has been conferred by a) target site mutation in the EPSPS gene, making it insensitive to the target protein (Kaundun et al 2011;Perez-Jones et al 2007;Yu et al 2007), b) reduced absorption and translocation of glyphosate (Dinelli et al 2008;Yu et al 2007;Wakelin et al 2004), c) increased glyphosate sequestration (Ge et al 2010), and d) EPSPS gene amplification (Chandi et al 2012;Gaines et al 2010;Jugulam et al 2014;Whitaker et al 2013). The presence of EPSPS gene copies (>100 copies) distributed throughout the genome has been confirmed in a GR Palmer amaranth biotype from Georgia (Gaines et al 2010). Additionally, EPSPS gene amplification has been reported in Palmer amaranth populations from North Carolina (Chandi et al 2012;Whitaker et al 2013), Mississippi (Ribeiro et al 2014), and New Mexico (Mohseni-Moghadam et al 2013a).…”
mentioning
confidence: 99%